2020
DOI: 10.24193/entomolrom.24.1
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the knowledge of the Lepidoptera of Vlăsia Plain (Muntenia, Romania)

Abstract: This study presents the results of an investigation carried out between 1966 and 2013, aiming to record the lepidoptera fauna of the Vlăsia Plain, a region centered on Bucureşti, Romania, and part of the more extensive Valahia Plain. 1251 lepidoptera representing 458 species were collected from forests, steppes, marshy areas and hilly zones situated between Bucureşti and the border of the Carpathian foothills. From these collections, 33 previously unrecorded species were added to the Valahia Plain checklist. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Ten of the latter are given here for the first time: Agonopterix bipunctosa (Curtis, 1850), A. coenosella (Zerny, 1940), A. ferocella ( Chrétien, 1910), A. irrorata (Staudinger, 1870), A. lessini Buchner, 2017, A. ligusticella (Chrétien, 1908 The examined material also provided data for 28 first records for the regions of Romania: 4 species in Dobrogea, 3 in Muntenia, 9 in Oltenia, 6 in Crișana and 6 in Transylvania. Further, one record for Banat (Székely and Cernea 2007), one for Muntenia (Albu and Albu 2020), and one for Transylvania (Székely and Görbe 2019) are mentioned. Five other earlier published records omitted by Rákosy et al (2003) were also identified and seven others must be deleted being based on misidentifications.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the latter are given here for the first time: Agonopterix bipunctosa (Curtis, 1850), A. coenosella (Zerny, 1940), A. ferocella ( Chrétien, 1910), A. irrorata (Staudinger, 1870), A. lessini Buchner, 2017, A. ligusticella (Chrétien, 1908 The examined material also provided data for 28 first records for the regions of Romania: 4 species in Dobrogea, 3 in Muntenia, 9 in Oltenia, 6 in Crișana and 6 in Transylvania. Further, one record for Banat (Székely and Cernea 2007), one for Muntenia (Albu and Albu 2020), and one for Transylvania (Székely and Görbe 2019) are mentioned. Five other earlier published records omitted by Rákosy et al (2003) were also identified and seven others must be deleted being based on misidentifications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on motor behavior are really important because the motor part is dominant in all the activities that an individual performs. Psychomotricity can be influenced in the first years of life, up to 11–12 years [ 9 ], and is a research topic even after this age for people with behavioral or mental disorders. In this case, depending on the severity of the neuromotor disorder, psychomotricity can be a concern for their whole life [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coordination includes oculo-motor and general dynamic coordination, and consists of the ability to associate movements in order to ensure efficient motor acts [ 9 , 49 , 50 , 51 ]. In order for movement to be adapted to a purpose, it must occur harmoniously in time and space, so it must be coordinated [ 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%